Ligand Displaces Heat Shock Protein 90 from Overlapping Binding Sites within the Aryl Hydrocarbon Receptor Ligand-binding Domain - Soshilov, Anatoly (American Society for Biochemistry and Molecular Biology, 2011)
Hsp90 (heat shock protein of 90 kDa) is often found associated with functional domains of client proteins, including those for ligand binding, dimerization, DNA binding, and enzymatic activity. Although Hsp90 can maintain the conformation of functionally important domains prior to activation of the client protein, its specific binding site and the mechanism(s) of Hsp90 dissociation during activation are unknown. Here, we have identified and characterized residues involved in Hsp90 binding within the aryl hydrocarbon receptor (AhR) ligand-binding domain and demonstrate that they overlap with those involved in ligand binding. In agreement with this spatial model, ligand binding results in Hsp90 dissociation from the AhR Per-ARNT-Sim B fragment. Interestingly, whereas Hsp90-binding residues within the ligand-binding domain were not involved in Hsp90-dependent AhR protein stability, several of these residues are important for ligand-dependent AhR activation, and their mutation resulted in conversion of two AhR antagonists/partial agonists into full AhR agonists. These studies reveal co-localization of a tentative Hsp90-binding site with that for AhR ligand binding and provide the first molecular mechanism for Hsp90 dissociation in the activation of a client protein.